Source-sink relationships in fruit species: A review - Fischer, Gerhard; Almanza-Merchán, Pedro José; Ramírez, Fernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2013)
ABSTRACTFruit production and quality depend on adequate source-sink relationships. Carbohydrates (CH) translocated from leaves or reserve organs are the most important for the growth and development of sink organs (mainly fruits). Up to 60% of CH produced daily can be lost through respiration. Carbohydrates constitute over 65% of the dry matter of tree crops. Increasing the leaf-fruit ratio generally increases fruit growth and CH content. Photosynthesis increases with fruit load and the leaves next to fruits are strong sources for CH. The leaf-fruit ratio is species, cultivar and geographic location dependent. The optimal leaf area in various species is 200 cm2 per 100 g of fruit.  Additional key words: carbohydrates, translocation, starch, leaf-fruit ratio.